2018
DOI: 10.1002/jib.505
|View full text |Cite
|
Sign up to set email alerts
|

Secretome analysis of Trichoderma reesei CICC41495 for degradation of arabinoxylan in malted barley

Abstract: Arabinoxylan, one of the major non‐starch polysaccharides of the endosperm cell wall of barley, has a negative impact on the filterability of wort and beer. The addition of microbial xylanase would be an effective strategy to degrade arabinoxylan. In this study, the secretome of Trichoderma reesei CICC 41495 cultivated under submerged fermentation with wheat bran as a carbon source was characterised by two‐dimensional electrophoresis combined with MALDI‐TOF/TOF tandem mass spectrometry. A total of 24 proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…However, the GH families of both AFases mentioned above are not clear. In this paper, only one AFase, which belongs to GH62, has been purified and identified, which is consistent with previous results [18]. The family GH62 exclusively contains AFases secreted by fungi or bacteria [15].…”
Section: Enzyme Purificationsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the GH families of both AFases mentioned above are not clear. In this paper, only one AFase, which belongs to GH62, has been purified and identified, which is consistent with previous results [18]. The family GH62 exclusively contains AFases secreted by fungi or bacteria [15].…”
Section: Enzyme Purificationsupporting
confidence: 90%
“…Reports concerning AFases from T. reesei are quite limited. In previous work, we have found a complete xylanolytic enzyme system in the culture filtrate of T. reesei CICC 41,495 by secretome analysis [18]. This research focusses on the AFase isolated from that crude mixture of xylanolytic enzymes.…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, Sun et al . , recently observed that the inclusion of a combination of xylanase enzymes from Trichoderma reesei with a mash decreased viscosity by 8%. These conclusions were in accordance to the observations by Schwarz and Han that arabinoxylan levels in commercial beers were ~10 times higher than those of β ‐glucans.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies on the arabinoxylan content in wort by Li et al (20) and particularly by Sadosky et al (19), have suggested that the contribution of arabinoxylan to viscosity is at least of equal importance to that of β-glucan. Accordingly, Sun et al (69), recently observed that the inclusion of a combination of xylanase enzymes from Trichoderma reesei with a mash decreased viscosity by 8%. These conclusions were in accordance to the observations by Schwarz and Han (70) that arabinoxylan levels in commercial beers were~10 times higher than those of β-glucans.…”
Section: Stepwise Multi-linear Regression To Predict Malt Extract Fementioning
confidence: 99%
“…Xylanase activity was measured using 1% (w/v) wheat arabinoxylan as substrate. Hydrolysis of the polymer was monitored using the dinitrosalicylic acid method (DNS) by measuring the reducing sugars from enzymatic activity at 540 nm (Sun et al, 2018). One unit of xylanase activity was defined as the amount of enzyme required to degrade xylan to produce 1 μmol xylose per minute under the conditions of the assay.…”
Section: Methodsmentioning
confidence: 99%